Science Embedded in Local Forest Landscape Management Improves Benefit Flows to Society - Langston, James Douglas; Riggs, Rebecca Anne; Kastanya, Agustinus; Sayer, Jeffrey; Margules, Chris; Boedhihartono, Agni Klintuni (Frontiers in Forests and Global Change, 2019)
There is a global shift of forest management to local levels to better reconcile local livelihoods and biodiversity conservation. We argue that achieving such outcomes will require embedding science in landscape-scale management systems. We show that science can contribute to local learning and adaptation within landscape contexts. Complexity and power relations have hampered scientists’ efforts to engage with the people who use and influence the use of resources at landscape scales. Landscape approaches present an opportunity for science to help steer local management to address local contexts. We have conducted research at the interface of policy and management at landscape scales. More effort must go towards transdisciplinary approaches to co-generate knowledge and create ‘Communities of Commitment’ for continual learning and adaptation amongst landscape-scale actors. Embedded science incorporating local knowledge and contexts and engaged in landscape scale development processes is necessary for improving decision and policy-making.